Finite element methods in civil and mechanical engineering : a mathematical introduction - Angoshtari, Arzhang; Matin, Ali Gerami (Boca Raton : CRC Press, 2020)
"The finite element method is widely employed for numerical simulations in engineering and science due to its efficiency. This concise introduction to the mathematical theory of the finite element method presents a selection of applications in civil and mechanical engineering such as beams and frames, Poisson's equation, heat transfer, advection-diffusion, linear elasticity, and incompressible fluids. Simple MATLAB codes and /or FENICS scripts of these examples can be downloaded from the book's companion website"--
OCLC-licensed vendor bibliographic record.
Keywords: Finite element method; Civil engineering -- Mathematics; Mechanical engineering -- Mathematics; TECHNOLOGY / Engineering / Mechanical; SCIENCE / Mechanics / General